Meningkatkan Motivasi Belajar Matematika melalui Model Pembelajaran Teams Games Tournament (TGT) di Kelas XI ULP 2 SMK N 4 Yogyakarta - Diaz Mayangkara; Faat Risnuriawan; Hanik Luluk Anifah; Richa Nurul Hidayati; Rita Purwani; Padrul Jana; Marsiyam Marsiyam (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2025)
Learning motivation plays a crucial role in supporting the effectiveness of classroom learning, particularly in increasing student engagement, encouraging active participation in the learning process, and optimizing learning outcomes. This study aimed to improve the low mathematics learning motivation of eleventh-grade students of ULP 2 at SMK N 4 Yogyakarta through the implementation of the Teams Games Tournament (TGT) cooperative model. This study employed a Classroom Action Research (CAR) approach, which was conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. Data were collected through learning motivation questionnaires, observation, and documentation, then analyzed descriptively quantitatively. The results of the study showed an increase in students' learning motivation, marked by an increase in the average motivation score in each cycle. This study achieved 78.5% at the end of the cycle and successfully achieved the set target of 75%. In conclusion, the implementation of the Teams Games Tournament (TGT) cooperative model is effective in increasing the mathematics learning motivation of eleventh-grade students of ULP 2 at SMK N 4 Yogyakarta.